2005
DOI: 10.1074/jbc.m414640200
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Up-regulates DNA-Protein Kinase-dependent p53 Activation to Enhance UVB-induced Apoptosis in Mouse Epithelial JB6 Cells

Abstract: In the present study, we employed a well established JB6 mouse epithelial cell model to define the molecular mechanism of efficacy of a naturally occurring flavonoid silibinin against ultraviolet B (UVB)-induced skin tumorigenesis. UVB exposure of cells caused a moderate phosphorylation of ERK1/2 and Akt and a stronger phosphorylation of p53 at Ser 15 , which was enhanced markedly by silibinin pretreatment. Kinase activity of ERK1/2 for Elk-1 and Akt for glycogen synthase kinase-3␤ was also potently enhanced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 49 publications
0
51
1
Order By: Relevance
“…Previous studies have reported that silibinin targets multiple signaling pathways, including those associated with oxidative stress and inflammation, to subsequently prevent tissue injuries and cancer by genotoxicity and other agents, which are similar to the pathways triggered following vesicant exposure (22,24,25). Therefore, silibinin was hypothesized to exhibit notable efficacy in attenuating MTX-induced lung injury, since MTX is known to trigger oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that silibinin targets multiple signaling pathways, including those associated with oxidative stress and inflammation, to subsequently prevent tissue injuries and cancer by genotoxicity and other agents, which are similar to the pathways triggered following vesicant exposure (22,24,25). Therefore, silibinin was hypothesized to exhibit notable efficacy in attenuating MTX-induced lung injury, since MTX is known to trigger oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown their capacity to decrease tumor cell proliferation and induce apoptosis in cancer cell lineages, endothelial cells, or normal cells exposed to carcinogenic stimuli. [5][6][7][8][9] The cornerstone of the proapoptotic action of silymarin/silibinin is the activation of the tumor suppressor gene p53. [6][7][8][9] Several downstream effectors of p53 activation have been implicated in silymarin-induced apoptosis, such as increased expression of proapoptotic Bax protein as well as reduction of the anti-apoptotic proteins Bcl-2, Bcl-xl, and survivin.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The cornerstone of the proapoptotic action of silymarin/silibinin is the activation of the tumor suppressor gene p53. [6][7][8][9] Several downstream effectors of p53 activation have been implicated in silymarin-induced apoptosis, such as increased expression of proapoptotic Bax protein as well as reduction of the anti-apoptotic proteins Bcl-2, Bcl-xl, and survivin. [6][7][8][9] In this study, we evaluated the effects of silymarin treatment on renal function and histopathology in glycerol-induced acute kidney injury (Gly-AKI) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data using mouse epidermal keratinocyte JB6 cells and ultraviolet light B have given insight into silibinin's activity with DNA-damaging agents. 41 In these experiments, the addition of silibinin increased the percentage of apoptotic cells when compared to the ultraviolet light B treatments alone. Silibinin's enhancement of ultraviolet light B- induced apoptosis was seen with an upregulation of DNA protein kinase, an important element in sensing genotoxic stress, with this effect abrogated by the addition of a semi-selective inhibitor of DNA protein kinase.…”
Section: Discussionmentioning
confidence: 89%
“…41,42 Of the 3 cell types examined here, LNCaP cells are considered to have wild type p53, PC-3 cells have a deletion in codon 138 with negative immunohistochemical staining for p53, and DU145 cells have 2 mutations in codons 223 and 274 of p53, but stain positive for p53 expression. 43 Notably, the PC-3 cells showed little apoptosis in response to either low-dose silibinin or mitoxantrone; however, the combination demonstrated a significant increase.…”
Section: Discussionmentioning
confidence: 99%